Posttraumatic Cognitions and Posttraumatic Stress Symptoms Among Young People Who Have Experienced Commercial Sexual Exploitation and Trafficking. (July 2022) - Perry, Elizabeth W.; Osborne, Melissa C.; Lee, NaeHyung; Kinnish, Kelly; Self-Brown, Shannon R.
Objectives: The impact of posttraumatic cognitions on the development and maintenance of posttraumatic stress symptoms (PTSS) is understudied among children and adolescents who have experienced commercial sexual exploitation/trafficking (CSE/T). The objectives of this study were to (1) explore posttraumatic cognitions among help-seeking young people aged 11-19 who have experienced CSE/T; (2) determine whether experiencing direct violence, witnessing violence, polyvictimization (ie, multiple exposures to different categories of potentially traumatic events), or demographic characteristics differentially affect whether these young people meet clinical criteria for posttraumatic cognitions using established cutoffs; and (3) explore associations between posttraumatic cognitions and PTSS among young people who have experienced CSE/T. Methods: This study is a secondary analysis of a baseline cross-sectional survey of 110 young people with substantiated CSE/T experiences who started trauma-focused cognitive behavioral therapy (mean [SD] age = 15.8 [1.5]) from August 1, 2013, through March 31, 2020, in a southeastern US state. We used descriptive statistics, adjusted modified Poisson regression, and adjusted linear regression to test study objectives. Results: Fifty-seven of 110 (51.8%) young people aged 11-19 met clinical criteria for posttraumatic cognitions. Increased age and a greater number of trauma categories experienced were significantly associated with meeting clinical criteria for posttraumatic cognitions. On average, higher posttraumatic cognition scores were associated with higher PTSS scores, controlling for demographic characteristics (β = 0.95; 95% CI, 0.64-1.26). Conclusions: These findings underscore the importance of assessing comprehensive trauma history and PTSS of young people who have experienced CSE/T, with added usefulness of measuring cognitive appraisals to inform a therapeutic treatment plan. Measuring cognitive appraisals that may influence PTSS and therapeutic success can ensure an effective public health response for this population.